High miR-124-3p expression identifies smoking individuals susceptible to atherosclerosis. (August 2017) - de Ronde, Maurice W.J.; Kok, Maayke G.M.; Moerland, Perry D.; Van den Bossche, Jan; Neele, Annette E.; Halliani, Amalia; van der Made, Ingeborg; de Winther, Menno P.J.; Meijers, Joost C.M.; Creemers, Esther E.; Pinto-Sietsma, Sara-Joan
Abstract: Background and aims: The risk of developing cardiovascular disease (CVD) is twice as high among smoking individuals compared to non-smokers. Monocytes are involved in smoking-related atherosclerotic plaque formation. In this study, we investigated whether smokers with an increased risk of developing CVD can be identified on the basis of monocyte-derived miRNA expression levels. Methods: We performed a miRNA microarray experiment on isolated monocytes from smoking, former smoking and non-smoking individuals in a cohort of patients with premature CVD and healthy controls (Cohort I, n = 76). Results: We found miR-124-3p to be heterogeneously expressed among all smoking individuals, whereas expression was low in non-smokers. Subsequently, RT-qPCR measurements on whole blood showed that among smoking individuals an increase in miR-124-3p is associated with an increased risk for advanced atherosclerotic disease (cohort II, n = 24) (OR 11.72 95% CI 1.09–126.53) and subclinical atherosclerosis (coronary artery calcium score ≥ 80 th percentile, cohort III n = 138) (OR 2.71, 95% CI 1.05–7.01). This was not observed among former smokers or non-smoking individuals. Flow cytometric analysis demonstrated that high miR-124-3p expression was associated with upregulation of the monocyte surface markers CD45RA, CD29 and CD206, indicating an altered monocyte phenotype. Finally, overexpression of miR-124-3p resulted in an upregulation of CD206 surface expression on monocytes. Conclusions: High miR-124-3p expression is associated with an increased risk of subclinical atherosclerosis in smoking individuals and with an altered monocyte phenotype. This may suggest that miR-124-3p identifies which smoking individuals are susceptible to the atherogenic effects of smoking. Highlights: MicroRNA-124-3p is upregulated in monocytes of smokers. High microRNA-124-3p expression in blood of smokers is associated with an increased risk of (subclinical) atherosclerosis. Monocyte microRNA-124-3p expression is associated with upregulation of the monocyte surface markers CD45RA, CD29 and CD206. Overexpression of microRNA-124-3p results in an upregulation of CD206 surface expression on monocytes.